The phytochemical and antibacterial activity of ethanolic extract of Laportea decumana and Laportea aestuans - Siahaya, Esty Vicariat; Kristiani, Elizabeth Betty Elok; Kasmiyati, Sri (Pharmaciana, 2025)
Plants have been an important medicinal resource for centuries, offering a rich source of bioactive compounds used in traditional and modern medicine. This study aims to analyze the comparison between Laportea decumana and Laportea aestuans, focusing on the two main aspects, phytochemical screening and antibacterial activity. The extraction of the maceration process uses ethanol 96% as the solvent at room temperature for 72 hours. The qualitative phytochemical analysis uses HCl and FeCl3 0.1% reagents to determine flavonoids and phenolic compounds, respectively. The quantitative analysis of total flavonoid content is measured using colorimetric AlCl₃ method, while the determination of phenolic compounds is performed by the Folin-Ciocalteu. The diffusion method is used to determine the antibacterial activity. The 96% ethanol extract of L. decumana leaves has higher flavonoids (69.4 mg GAE/g extract) than phenolics (55.1 mg QE/g extract). However, the L. aestuans has higher phenolic content (55.3 mg QE/g extract) than flavonoids (35.3 mg GAE/g extract). The antibacterial test using agar diffusion method shows that both extracts inhibited the growth of pure strains of E. coli ATCC and S. aureus ATCC, with different potencies. The L. decumana extract showed 1.5 times stronger activity than the L. aestuans extract on the growth inhibitory activity against E. coli bacteria. The results show that the relationship between the antibacterial activity and the phytochemical profile against E. coli is strong but weak against S. aureus.